2021
DOI: 10.1192/j.eurpsy.2021.2249
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on shared biological mechanisms of depression and anxiety in comorbidity with psoriasis, atopic dermatitis, and hidradenitis suppurativa

Abstract: Background Mental disorders in comorbidity with chronic skin diseases may worsen disease outcome and patients’ quality of life. We hypothesized the comorbidity of depression, anxiety syndromes, or symptoms as attributable to biological mechanisms that the combined diseases share. Methods We conducted a systematic review based on the Preferred Reporting Items for Systematic Review and Meta-Analysis statement searching into PubMed, PsycInfo, and Scopus databases. We examined the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 81 publications
(117 reference statements)
2
28
0
1
Order By: Relevance
“…Psychiatric comorbidities seem to be common among patients suffering from chronic inflammatory diseases, including psoriasis, atopic dermatitis and HS [11,12]. Our study, based on the Polish cohort of HS patients clearly confirmed these findings.…”
Section: Discussionsupporting
confidence: 85%
“…Psychiatric comorbidities seem to be common among patients suffering from chronic inflammatory diseases, including psoriasis, atopic dermatitis and HS [11,12]. Our study, based on the Polish cohort of HS patients clearly confirmed these findings.…”
Section: Discussionsupporting
confidence: 85%
“…Our overall clinical judgment was that the severity of psoriasis occurred in parallel with depressive symptoms, thus indicating a possible correlation between psoriasis and depression [ 48 ]. In fact, psoriasis and depression are reported to share biological mechanisms such as the high levels of proinflammatory cytokines interleukin (IL)-1 and IL-6, thus showing that an inflammatory process might be involved in both diseases progressing [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increasing evidence showing the bidirectional relations between psychological factors and AD ( Fabrazzo et al, 2021 ; Huet et al, 2022 ). However, there are very few animal experimental studies on this subject, leaving two key points unclear, namely, the characteristics of negative mental states and their underlying mechanism in AD mice.…”
Section: Discussionmentioning
confidence: 99%